(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Background: Vidarikand is the one of the most important drug which has broadly described in detail in all the textbook of Ayurveda. It is commonly known as Indian kudzu which is a perennial climber with woody tuberculated stem with large tuberous roots. Generally all the Nighantus are mention its various properties. It is used in variety of formulation mention in Ayurvedic Samhita for the different-different purpose and treatment of diseases. There are so many researches were done on Vidarikand on range of diseases and its property. Aims and Objects: This paper trying to elaborate, evaluate and discuss the medicinal property, therapeutic effects of Vidarikanda in various diseases including new emerging problems. Material and Method: The text book of Ayurveda, its commentaries and text book of modern medicine along with various clinical studies published in index journal have been review thoroughly. Result and Discussion: Vidarikanda has Madhur Rasa,Shita Veerya and Guru, Snigdh Guna and it pacify Vata, Pitta and Rakta dosha and having Brihani, Vrashya, Jivniya, Rasayan, Stanya, Shukral, Balya property mention in Ayurvedic text due to these excellent property its field of use is highly amplified for cure diseases. Its formulations are highly used in Jwara, Raktapitta, Rajayakshma, Apasmar, Kshatksina, Kasa, Vatavyadhi, Vatarakta, Klevya and many more diseases. It is also mentioned in Balavarna vardhak and Vranaropak formulation. It is good in Immunomodulting, Antioxidant, Galactogogue, Cardiotonic, Aphrodisiac, Rejuvenation, Nootropic and Anti-inflammatory effect.